Development of Eucalyptus Fiber Masterbatch for Polyethylene Additives - Ilana O. Almeida; Talyta S. Prado; Lucas N. Horiuchi; Rosana L. Fialho; Joyce B. Azevedo (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Growing concerns about sustainability and environmental impact have driven the development of alternative materials, such as polymer composites reinforced with natural fibers. However, a gap remains between scientific advances and large-scale industrial applications of these composites. This study aimed to develop eucalyptus fiber masterbatches as an alternative to optimize the production of high-density polyethylene (HDPE) composites. To obtain the masterbatches, high fiber concentrations (30%, 40%, and 50%) were incorporated into HDPE using twin-screw extrusion. From the 50% concentrate, composites containing 10% fiber were subsequently produced. Optical microscopy analysis showed good fiber dispersion and distribution in the polymer matrix, with an estimated average length of 7.48 mm. Mechanical testing revealed that, although fiber addition reduced tensile strength, it increased the elastic modulus, indicating structural reinforcement. In terms of impact strength, no changes were observed in the composite produced from the masterbatch, confirming adequate fiber distribution and the absence of agglomerates. Overall, the results demonstrate the feasibility of using eucalyptus fiber as reinforcement in HDPE composites produced from fiber concentrates.